Pemanfaatan Media Website “Mantes” untuk Meningkatkan Pengetahuan Masyarakat tentang Cek Kesehatan - Sekar Okta Deliana; Achmad Lukman Hakim; Emi Oktavia Sari; Hikmah Apriyanti; Syifa Pauziah (Jurnal Pengabdian Masyarakat Saga Komunitas, 2023)
Introduction: Currently Indonesia ranks seventh out of ten countries with the highest prevalence of diabetes mellitus at 10.6% of the total population. Depok City is the area with the highest DM incidence rate in West Java, namely 2.9% of the population. Objectives: This Field Study Practice III aims to educate the importance of health checks, especially for people who have a hereditary history of diabetes mellitus by using the website "Bersama Lawan Diabetes" at the UPTD Puskesmas Sukmajaya, Depok City in 2022. Method: The method of socialization that we used is giving lectures, assignments, discussions, and the presentation which was held on November 15 2022 with the target of the activity namely 15 patients in the working area of ​​the UPTD PKM Sukmajaya, both diabetes patients and general patients. This community service activity was successful, as seen from the enthusiasm of the participants and increased knowledge as seen from the results of the pre-test and post-test where the data were managed using Microsoft Office. Result: After counseling, 13 out of 15 participants experienced an increase in knowledge, whereas previously the pretest results showed only 5 out of 15 who only managed to answer questions correctly. Conclusion: Based on the results of the activities above, it can be concluded that there are differences in community knowledge before and after the implementation of socialization regarding the use of the MANTES website. there is an increase in knowledge and understanding of the importance of routine health checks after this community service is held.